Effect of Auricular Acupress Therapy on Insomnia of Cancer Patients : Randomized, Single Blinded, Placebo Controlled Trial - In-Sook Jung; Jungsun Kim; Hwa-Seung Yoo (Korean Pharmacopuncture Institute, 2010)
Background: Auricular acupressure is one of the traditional health care treatments in oriental medicine. Approximately, 30~40% of the cancer patients have said to be suffering from insomnia and half of them having chronic and severe insomnia at the same time. Insomnia caused cancer patients feel more pain, fatigue, depression and anxiety and it sometimes let the power to have the best of cancer pull down. Objective: To investigate how effective the auricular acupressure treatment to cancer patients suffering from insomnia. Methods: We recruited participants from East-West Cancer Center of Daejeon University. Finally, of the people whose age range from 20 to 75, 12 patients who got less than 40 points from the score of Oh's sleeping score (OSS) were recruited. Single-blind, randomized pilot study was performed. The treatment group received auricular acupressure treatment (AAT) on active points and the control group had received sham acupressure treatment (SAT) for five times. Sleep parameters were checked by using OSS and numeric rating scale (NRS). We checked the scale everytime, both before and after treatment. We analyzed the data statistically by using independent T-test, paired T-test and analysis of variance (ANOVA) test. (p<0.05) Results: Twelve cancer patients participated in this pilot study and there was no significant difference between control and treatment group. Only 7 of them had completed the whole treatment process, 4 patients of AAT group and 3 participants of SAT. The OSS of AAT group had increased from 34.0± 4.3 to 39.5±3.1 and that of SAT group had increased from 38.3±3.5 to 40.0±0.0. There was no significant difference between them. The NRS of AAT group had increased from 6.3±2.9 to 4.8±2.1 and that of SAT group had increased from 7.0±1.0 to 5.0±2.6. No significant difference was observed between them. Conclusion: Although both groups did not show significant differences, most of the experimental participants showed increasing OSS and NRS after treatments. Significant participants' number will be needed in the next study.